Exploration of Spatial Design and Interactive AI in Development of 3D Audio Games for Visually Impaired Players: A Systematic Literature Review - Kurniawan Kaka; Agus Juhana (Politeknik Negeri Media Kreatif, 2026)
The paradox of digital accessibility in the global gaming industry has systematically marginalized more than 2.2 billion visually impaired people, creating an immersion gap between visual and auditory gaming experiences. This study investigates the integration of 3D audio games and AI based voice assistants to create immersive and inclusive gaming experiences through a Systematic Literature Review (SLR) using the PRISMA framework and snowballing technique. 975 studies identified, 56 articles met the inclusion criteria after a rigorous selection process. The synthesis results reveal key findings, namely that immersive 3D audio design requires spatial audio precision, adaptive sonification, and haptic feedback to help players build mental maps of the virtual environment. Additionally, the need for narrative design and voice-based interaction emphasizes the importance of exploration flexibility, audio information balance, and adaptive narrative systems capable of adjusting responses based on situational context. Furthermore, the integration of artificial intelligence as an interactive companion plays a crucial role in providing contextual narratives and spatial navigation guidance through two-way voice interaction. The research conclusion affirms that the synergy between spatial audio technology, adaptive narrative design, and artificial intelligence creates a new paradigm in inclusive game design, where sound is no longer merely a substitute for visuals but the primary medium that unifies perception and interaction in an equitable gaming experience.